Alice's Adventures: The Complete Visual Guide - Elizabeth Dowsett, Jo Casey & Laura Gilbert
Join Alice as she returns to the big screen and to Underland. Alice's The Complete Visual Guide includes all of Alice's whimsical adventures from Alice Through the Looking Glass as well as from Alice in Wonderland.Alice's The Complete Visual Guide explores all the Alice in Wonderland strange landscapes, key themes, fantastical scenes and curious characters like the Mad Hatter, the grinning Cheshire Cat, and the terrifying Jabberwocky, from both the latest film and the first one. Plus special features let you explore the Red Queen's castle, take tea at the March Hare's party and marvel over the Mad Hatter's crazy collection of hats.Alice's The Complete Visual Guide is the perfect book for any Alice fan.